Functional Improvement of Non-State Pension Funds as Mechanism of Investment in Russian Economy - Guseva, Irina A.; Kulikova, Elena I.; Rebelsky, Nikolay M.; Arkhipova, Lidia S. (Journal of Reviews on Global Economics, 2018)
The article is dedicated to the search of investments in the domestic financial market that is a relevant problem for the Russian economy. The authors believe that pension funds attracted by non-state pension institutions are an essential resource for the Russian economy; practices of foreign pension institutions need to be examined and implemented to tap this resource more efficiently. The proposed measures specified in the article following the study of foreign pension funds’ functioning include: changes in the criteria for balancing portfolios of Russian pension funds’ securities; development of new instruments for pension funds’ investment; enhancing activities of non-state pension funds’ shares market; activation of pension funds’ investments in shares of innovative enterprises, etc. Practical proposals on the improvement of Russian non-state pension funds’ activities have been made.